2018
DOI: 10.1016/j.jmir.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study on the Role of Ultrasound Imaging of Bladder Volume as a Method to Improve Concordance of Bladder Filling Status on Treatment with Simulation

Abstract: Purpose: Accurate positioning of the prostate is of paramount importance to ensure optimal target coverage and normal tissue sparing in stereotactic ablative body radiation when large doses per fraction are delivered with tight margins around the prostate. Bladder and rectal filling play an important part in controlling the accuracy of a patient's setup and therefore the overall toxicities and outcomes. The aim of this study was to establish the value of characterizing patients' bladder filling kinetics at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…5 Analyses on optimal bladder filling have shown that it takes about 57 to 75 minutes after consumption of 500 cm 3 of water to achieve bladder filling measured at 180 cm 3 . 3,6 These studies, however, did not analyze the effect of bladder filling variability on dosimetry.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5 Analyses on optimal bladder filling have shown that it takes about 57 to 75 minutes after consumption of 500 cm 3 of water to achieve bladder filling measured at 180 cm 3 . 3,6 These studies, however, did not analyze the effect of bladder filling variability on dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol is either based on treatment with a "comfortably full-bladder" or one that is centered around a voiding-filling-timing regimen to replicate the bladder filling at time of computed tomography (CT) simulation. [1][2][3][4][5][6] Treating patients with a full bladder is based on established dosimetric studies that demonstrate better sparing for the bladder and other organs at risk. 2,[7][8][9][10][11][12][13] However, studies based on daily and weekly on-treatment imaging have shown that bladder filling varies and can result in dosimetric variances that differ from the initial CT scan (and planning dose volume histogram [DVH]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations